Modeling of a Concrete Dam under Earthquake Loading by A Nonlocal Microplane Approach. (2017) - Indriyantho, Bobby Rio; Zreid, Imadeddin; Kaliske, Michael
Abstract: The response of concrete under dynamic loading is different from static cases. Substantial increase in strength and changing of crack patterns are observed with an increased loading rate. Modeling of dynamic behavior and failure of concrete is a crucial aspect for the correct simulation and safety of structures subjected to seismic loadings. The microplane approach offers a straightforward way to model the induced anisotropy in concrete by defining the constitutive material relations between stress and strain vectors on randomly oriented planes. In this contribution, the work will be focused on the formulation and the implementation of a microplane model to describe the behavior of concrete under dynamic loading. Furthermore, the rate of dependency of the concrete as well as the inertia effects will be included in the model, which are essential for the dynamic case. Finally, the model will be implemented within a nonlocal implicit gradient enhanced framework in order to eliminate the pathological mesh sensitivity. A concrete gravity dam will be investigated as a numerical example to demonstrate the capabilities of the new formulation. The proposed model is used successfully to model the dam under earthquake loading.